Information Systems: Applications in Smart Cities, Smart Buildings and Smart Life - BARACHO, RENATA ABRANTES (Qualitative and Quantitative Methods in Libraries, 2019)
This paper presents a proposal for an information system for the interdependent ecosystem that includs Smart Cities, Smart Buildings, and Smart Life with connections to Smart Business and Industry. We argue for the importance of Knowledge Organization Systems - KOS for the integration of many specialized information systems and insights gained from machine learning, which in turn supports the integration and mutual reinforcement of activities in planning, building, and operating smart cities and smart buildings. These activities serve real human needs, improving the quality of life and the efficiency of life activities. Such a Knowledge Organization System would allow us to map in detail the complex interactions of the many processes, objects, and factors in the interdependent ecosystem. It would facilitate the application of artificial intelligence (AI). It would allow us to connect key human needs to available resources and to work towards a sustainable planet. The paper illustrates the interdependent ecosystem through several examples, discusses the contributions of KOS and models, presents first thoughts on how a comprehensive Knowledge Organization System might be structured, and culminates in the proposal of developing such a KOS on a collaborative platform.